UPAYA ALIBABA DALAM MENANGANI COUNTERFEIT GOODS ASAL TIONGKOK - Ovi Nurtri Asih; Reni Windiani (Journal of International Relations Diponegoro, 2019)
Counterfeit goods is a global problem that does not only occur in one country but many, including Tiongkok. Along with developments in technology, Counterfeit goods does not only occur offline but also online. Various efforts have been made to deal with the problem in Tiongkok. Although a lot has been sought, it still persists. Clearly other efforts are needed to deal with the problems. This study aims to explain the efforts that can be made by Alibaba as one of the transnational companies in handling counterfeit goods from Tiongkok in years 2013-2018. The theory used in this study is theory of securitization by Barry Buzan. The method used in this study is a qualitative method, with the type of analysis description research through data collection techniques and literature studies. The results of this study are the efforts made by Alibaba as a transnational company in handling counterfeit goods in Tiongkok, through securitization. Securitization carried out by Alibaba with various ways, such as cooperating with the International Anti Counterfeiting Coalition (IACC) and by establishing Alibaba Anti counterfeiting Alliance (AACA). Alibaba has an important role in helping Tiongkok government to deal with counterfeit goods, mainly online. Still, securitization efforts carried out by Alibaba required support from Tiongkok government as actors who could make legal and binding policies.